Disaster Labs : How American States Use Partnerships to Manage the Unthinkable - Givens, Austen D., 1982- (Book collections on Project MUSE., 2020)
"Disaster Labs examines the promise and potential drawbacks of public-private disaster response frameworks during the course of seven chapters. After the introduction, the author introduces a series of case studies and then provides a detailed discussion of public-private collaboration in California, Florida, New York, and Virginia. A concluding chapter then comparatively assesses the value of these partnerships. The cases discussed in Disaster Labs range from informal ad hoc collaborations to formalized initiatives with detailed structures defined in contracts and memoranda, setting expectations for performance and accountability for both the government and private actors. Such accountability is desirable as it can limit fraud and corruption. But it is important to emphasize that not all solutions work in all situations, either"--